Избавьтесь от иррациональности в знаменателе

vlabiclavakozlova vlabiclavakozlova    1   28.02.2019 05:30    1

Ответы
ВероникаПлюс ВероникаПлюс  23.05.2020 16:35

1\(1+корень(2)+корень(3))=

(1+корень(2)-корень(3))\(1+корень(2)-корень(3))(1+корень(2)+корень(3))=

=(1+корень(2)-корень(3))\(1+2+2*корень(2)-3)=

=1\2*(1+корень(2)-корень(3))\корень(2)=

=1\4*корень(2)*(1+корень(2)-корень(3))=

=1\4*(-корень(6)+корень(2)+2)

ответ:(-корень(6)+корень(2)+2)\4

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра